Perspectives and Emerging Issues of Uganda’s External Development Finance Landscape - Munyambonera Ezra, Francis; Nagawa, Maria (Economic Policy Research Centre, 2017)
During the past 15 years, Uganda has witnessed a significant change in the mode and form of external development finance (EDF) received. Traditionally, Uganda has largely sourced its EDF from the Organization for Economic Cooperation and Development –Development Assistance Committee (OECD-DAC) and from multilateral development institutions. On the other hand, landscape in an environment characterized by the emergence of new donors like China, South Korea, and India, among others. This brief describes the extent of the changes in EDF and how different stakeholders are responding to the changing access to and utilization of external funds.